Anti-biofouling and functionalizable bioinspired chitosan-based hydrogel coating via surface photo-immobilization. Issue 5 (24th March 2019) - Xv, Jiesheng; Li, Haoying; Zhang, Wenrui; Lai, Guichao; Xue, Haoyu; Zhao, Jianhao; Tu, Mei; Zeng, Rong
Abstract: Zwitterionic polymer is a new generation of anti-fouling materials with its good resistance to protein and bacterial adhesion. Constructing the anti-fouling surfaces with zwitterionic polymer has been regarded as an effective approach for improving the biocompatibility and biofunctionality of clinic devices. Herein, we reported a facile approach to construct a biodegradable anti-biofouling and functionalizable hydrogel coating via photo-immobilization using commercial polyethylene terephthalate (PET) films as the substrate, based on zwitterionic glycidyl methacrylate-phosphorylcholine-chitosan (PCCs-GMA). The surface structure and physicochemical properties of zwitterionic PCCs-GMA hydrogel coating were investigated by X-ray photoelectron spectroscopy (XPS), atomic force microscope (AFM) and static water contact angle measurement, and its functionalizable sites were detected by fluorescence labeling. Compared with the pristine PET and cationic chitosan - GMA and hydroxypropyltrimethyl ammonium chloride chitosan (HTCC) - GMA hydrogel coatings, zwitterionic PCCs-GMA hydrogel coating exhibited excellent biocompatibility, and significantly reduced protein adsorption for three model proteins of fibrinogen, immunoglobulin and lysozyme, repelled platelet adhesion, as well as showed a high resistance to bacterial attachment of Escherichia coli and Staphylococcus aureus and superior anti-fouling properties to MRC-5 cells. The results indicated that photo-immobilized zwitterionic PCCs-GMA hydrogel coating has perspective as a dual functional platform with integrated antifouling and further biofunctional properties for various biomedical applications.